Optimized inducible shRNA and CRISPR/Cas9 platforms for in vitro studies of human development using hPSCs - Bertero, Alessandro; Pawlowski, Matthias; Ortmann, Daniel; Snijders, Kirsten; Yiangou, Loukia; Cardoso de Brito, Miguel; Brown, Stephanie; Bernard, William G.; Cooper, James D.; Giacomelli, Elisa; Gambardella, Laure; Hannan, Nicholas R.F.; et al. (Company of Biologists, 2016)
Inducible loss of gene function experiments are necessary to uncover mechanisms underlying development, physiology and disease. However, current methods are complex, lack robustness and do not work in multiple cell types. Here we address these limitations by developing single-step optimized inducible gene knockdown or knockout (sOPTiKD or sOPTiKO) platforms. These are based on genetic engineering of human genomic safe harbors combined with an improved tetracycline-inducible system and CRISPR/Cas9 technology. We exemplify the efficacy of these methods in human pluripotent stem cells (hPSCs), and show that generation of sOPTiKD/KO hPSCs is simple, rapid and allows tightly controlled individual or multiplexed gene knockdown or knockout in hPSCs and in a wide variety of differentiated cells. Finally, we illustrate the general applicability of this approach by investigating the function of transcription factors (OCT4 and T), cell cycle regulators (cyclin D family members) and epigenetic modifiers (DPY30). Overall, sOPTiKD and sOPTiKO provide a unique opportunity for functional analyses in multiple cell types relevant for the study of human development.